2021
DOI: 10.1183/13993003.01876-2021
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the power of anticipation to manage respiratory-related brain suffering and ensuing dyspnoea: insights from the neurobiology of the respiratory nocebo effect

Abstract: The mere expectation of dyspnoea contributes to shape the lives of patients with chronic respiratory diseases: approaches addressing anticipatory mechanisms will provide new therapeutic avenues for persistent dyspnoea in the near future https://bit.ly/3mkv6USCite this article as: Vinckier F, Betka S, Nion N, et al. Harnessing the power of anticipation to manage respiratory-related brain suffering and ensuing dyspnoea: insights from the neurobiology of the respiratory nocebo effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“… 79 97 Since expectation of dyspnoea can be manipulated by an external intervention, it becomes of major importance not only to interfere with acute brain mechanisms, but also to reverse chronic conditioning to free the patient’s mind from negative respiratory anticipation. 97 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 79 97 Since expectation of dyspnoea can be manipulated by an external intervention, it becomes of major importance not only to interfere with acute brain mechanisms, but also to reverse chronic conditioning to free the patient’s mind from negative respiratory anticipation. 97 …”
Section: Resultsmentioning
confidence: 99%
“…79 97 Since expectation of dyspnoea can be manipulated by an external intervention, it becomes of major importance not only to interfere with acute brain mechanisms, but also to reverse chronic conditioning to free the patient's mind from negative respiratory anticipation. 97 In oncology, the experimental tradition in placebo and nocebo effects originated in the study of anticipatory nausea in chemotherapy. The latter refers to the phenomenon whereby patients develop such strong learning between their chemotherapy context and the nausea that they begin to feel nauseous purely when they re-enter this context.…”
Section: Continuedmentioning
confidence: 99%
“…Dyspnoea is a symptom but it is also an experience that changes the brain of those afflicted (through memory/ anticipation phenomena, see refs. [5][6][7] ) and therefore shapes their lives. 8,9 This is particularly true when dyspnoea continues despite maximal pathophysiological treatments (persistent dyspnoea).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, several variables including pain expectations can partially explain the relationship between unpredictability and pain perception (62-64). Such effects have not yet been systematically confirmed for breathlessness, although research has already repeatedly suggested comparable influences of expectations on breathlessness perception in both clinical and non-clinical samples (22,(65)(66)(67)(68)(69)(70). Negative expectations are also an important element of catastrophizing, itself associated with worse quality of life (71).…”
Section: Implication For Future Research and Clinical Practicementioning
confidence: 99%